Petrogenesis of the late Tonian arc-related Um Balad gabbro-diorite complex (Egypt) and insight into its spatially related orogenic gold mineralization. Issue 1 (2nd January 2023) - Abd El-Rahman, Yasser; Seifert, Thomas; Schulz, Bernhard; Hofmann, Mandy; Gärtner, Andreas; Linnemann, Ulf; Said, Amir
ABSTRACT: The gabbro-diorite complex of the Um Balad prospect hosts lode gold mineralization. The complex is dated at 723 ± 4 Ma using the LA-ICP-MS U-Pb zircon method and is correlated with the late Tonian-early Cryogenian subduction-related magmatic stage during the evolution of the Arabian-Nubian Shield. The gabbro-diorite complex evolved through the crystallization of a calc-alkaline magma and the subduction signature of this magma is verified by primitive mantle-normalized trace element patterns that show enrichment in large ion lithophile elements, U, and Th relative to high field strength elements as well as negative Nb and Ti anomalies. The high La/Ybcn (3.1–9.4) and Ta/Yb (0.12–0.41) ratios are consistent with a continental arc rather than an oceanic arc system. Amphibole chemistry indicates that this complex might have crystallized under a moderately oxidizing condition from a hydrous magma (>6 wt% water content) at temperature and pressure estimates of about 800°C and 3 kbar, respectively. Gold mineralization in the Um Balad prospect is confined to structurally controlled massive quartz±carbonate veins and surrounding alteration halos. Alteration in the prospect is represented by localized sericitization and carbonation as well as pervasive chlorite-sericite alteration. The alteration halos are characterized by enrichment in K and Rb and depletion in Ca and Sr compared to their host rocks. The veins of the prospect are related to lower order extensional fractures associated with the regional first order transpressional Najd Fault System. The high Fe contents of the gabbro-diorite complex represent a suitable chemical trap for gold through sulfidation of the host rocks. Supergene alteration resulted in the formation of goethite in association with atacamite and chrysocolla. Free mill gold is associated with these supergene phases, which were deposited in near neutral to slightly alkaline conditions.